1995
DOI: 10.1074/jbc.270.29.17344
|View full text |Cite
|
Sign up to set email alerts
|

Insect Cells Contain an Unusual, Membrane-bound β-N-Acetylglucosaminidase Probably Involved in the Processing of Protein N-Glycans

Abstract: The beta-N-acetylglucosaminidase activity in the lepidopteran insect cell line Sf21 has been studied using pyridylaminated oligosaccharides and chromogenic synthetic glycosides as substrates. Ultracentrifugation experiments indicated that the insect cell beta-N-acetylglucosminidase exists in a soluble and a membrane-bound form. This latter form accounted for two-thirds of the total activity and was associated with vesicles of the same density as those containing GlcNAc-transferase I. Partial membrane associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
138
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(157 citation statements)
references
References 15 publications
18
138
1
Order By: Relevance
“…It is noteworthy that this enzyme could not hydrolyze Man5Gn, 4 but acted only further "downstream" on MGn and GnGn where it specifically removed GlcNAc-1 (20). Subsequent cell culture experiments in the presence of hex-osaminidase inhibitors (7,11,21) or of recombinant ␤1,4-galactosyltransferase (22,23) corroborated the putative existence of a processing hexosaminidase.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…It is noteworthy that this enzyme could not hydrolyze Man5Gn, 4 but acted only further "downstream" on MGn and GnGn where it specifically removed GlcNAc-1 (20). Subsequent cell culture experiments in the presence of hex-osaminidase inhibitors (7,11,21) or of recombinant ␤1,4-galactosyltransferase (22,23) corroborated the putative existence of a processing hexosaminidase.…”
mentioning
confidence: 53%
“…Incubation was terminated by the addition of 0.18 ml of 20 mM ice-cold sodium borate. Aliquots of 0.05 ml were analyzed by reverse-phase HPLC as described previously (15,20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside the vertebrate subphylum, invertebrates such as Caenorhabditis elegans (16,18,(22)(23)(24) and Drosophila melanogaster (15,17,25,26), plants (27), and other "lower" organisms (28) abundantly produce protein paucimannosylation. Paucimannose synthesis in these species is facilitated by high ␤-Nacetylhexosaminidase activity, allowing partial suppression of the complex N-glycan biosynthetic route.…”
mentioning
confidence: 99%
“…Enrichment of Hex B and B-like Hex isoenzymes was also described in the PM fraction of HL 60 leukemic cell line (Martino et al, 1995), where its activity is modulated by cell differentiation (Emiliani et al, 1995c). Altmann et al (1995) demonstrated that in Sf-i insect cells Hex exists in a soluble and a membrane-bound form and that the latter is probably involved in the processing of Nglycan proteins.…”
Section: Discussionmentioning
confidence: 99%